Hydrogen Flux through Size Selected Pd Nanoparticles into Underlying Mg Nanofilms. Issue 4 (22nd September 2017) - Kumar, Sushant; Pavloudis, Theodore; Singh, Vidyadhar; Nguyen, Hoa; Steinhauer, Stephan; Pursell, Christopher; Clemens, Bruce; Kioseoglou, Joseph; Grammatikopoulos, Panagiotis; Sowwan, Mukhles
Abstract: The application of Mg for hydrogen storage is hindered due to the slow absorption of hydrogen in Mg films. Herein, the hydrogenation process is explored theoretically using density functional theory calculations, and energy barriers are compared for hydrogen diffusion through Pd nanoparticle/Mg film interfaces and their variations, i.e., Pd(H)/Mg(O). Decomposing the mechanism into basic steps, it is shown that Pd undergoes a strain‐induced crystallographic phase transformation near the interface, and indicated that hydrogen saturation of Pd nanoparticles enhances their efficiency as nanoportals. Using energetic arguments, it is explained why hydrogen diffusion is practically prohibited through native Mg oxide and seriously suppressed through existing hydride domains. Hydrogen flux is experimentally investigated through the nanoportals in Pd‐nanoparticle decorated Mg films by pressure‐composition isotherm measurements. An r ≈ t 1/3 relationship is theoretically calculated for the radial growth of hemispherical hydride domains, and this relationship is confirmed by atomic force microscopy. The diffusion constant of hydrogen in Mg films is estimated as D H film ≈ 8 × 10 −18 m 2 s −1, based on transmission electron microscopy characterization. The unique nanoportal configuration allows direct measurement of hydride domain sizes, thus forming a model system for the experimental investigation of hydrogenation in any material. Abstract : Pd nanoparticles deposited on Mg films locally inhibit their oxidation, enabling hydrogen diffusion through the developed interface, as demonstrated by density functional theory calculations. This unique nanoportal configuration enables direct observation of distinct hydride domains, thus allowing the investigation of hydrogen flux into Mg films and the determination of the apparent diffusion coefficient, with a view to hydrogen storage applications.